Functional recovery after knee arthroplasty with regional analgesia: A systematic review and meta-analysis of randomised controlled trials. Issue 6 (June 2019) - Osinski, Thomas; Bekka, Samir; Regnaux, Jean-Philippe; Fletcher, Dominique; Martinez, Valeria
Abstract : BACKGROUND: Regional analgesia (RA) has been widely evaluated for pain relief after total knee arthroplasty (TKA). Its impact on functional recovery is less well known. OBJECTIVES: To evaluate the functional benefits of RA after TKA. DESIGN: Systematic review with a random-effects meta-analysis of randomised controlled trials comparing LRA with systemic analgesia on function in adults undergoing TKA for osteoarthritis. DATABASE SOURCES: MEDLINE, EMBASE, LILAC, Cochrane, CTRD databases. OUTCOMES: Length of stay (LOS) in hospital and early knee flexion range of motion (ROM), early and long-term knee function, serious adverse effects. RESULTS: Twenty-three studies (1246 patients) were included. LOS was significantly shorter for RA than for systemic analgesia (0.90 days, 95% confidence interval 0.3 to 1.4). Subgroup analyses found that only infiltration analgesia decreased the LOS. ROM during the first week was significantly higher for all techniques of RA than for systemic analgesia (9.23°, 95% confidence interval 4.6 to 13.9). No impact of regional analgesia techniques on global function in the longer term was demonstrated. No difference in serious adverse effects was found between RA and systemic analgesia. CONCLUSION: RA techniques compared with systemic analgesia have a beneficial impact on the LOS and the ROM achieved in the early postoperative period. Global function in the longer term after surgery seems unaffected by peri-operative RA. TRIAL REGISTRATION: CRD42014013995. Abstract : Supplemental Digital Content is available in the text